Preferences for the sequencing of first-line systemic treatments in metastatic hormone receptor-positive, HER2-negative breast cancer - Al Mahmasani, Layal; Amhaz, Ghid; Abou Zeidane, Reine; Chamseddine, Nathalie; Hatab, Taha; Sabbagh, Saad; Charafeddine, Maya; Assi, Hazem I. (Frontiers in Oncology, 2023)
Introduction: Metastatic breast cancer (MBC) is a diverse disease. Therapeutic options include hormonal therapy, chemotherapy, and targeted therapies. The optimal treatment sequence for patients with hormone receptor-positive (HR-positive), HER2-negative metastatic breast cancer remains unknown.Methods: This was a retrospective and prospective study. The data was collected from the medical records of patients in a tertiary healthcare center in Lebanon between the years 2016 and 2019, and patients were followed up for a 3-year duration. The main aim was to identify oncologists' preferences in the choice and sequence of treatment for newly diagnosed and/or recurrent cases of HR-positive, HER2-negative MBC.Results: A total of 51 patients were included. 24 patients received chemotherapy, while 27 received endocrine therapy as first-line treatment after a diagnosis of MBC, with a median overall survival (OS) of 13 months and a median progression-free survival (PFS) of 12 months after first-line treatment with chemotherapy, compared to 27 months and 18 months with endocrine therapy. A higher percentage of patients have received chemotherapy in the first-line setting compared to the data reported in the literature, with the choice being multifactorial. This is a provisional file, not the final typeset article Conclusion: Factors to consider in MBC management include the choice of first-line treatment, the optimal sequence of treatment, and the combination of available treatment options.